THE SOCIAL CHANGES IN AMERICA AS REFLECTED IN HEAD OF STATE MOVIE - Marcelia, Marla (LANTERN (Journal on English Language, Culture and Literature), 2015)
In America, we know an interesting fact that Americans had chosen their first black President. It is a rare event because it is the first time for the United States of America to be lead by an African American man. In the progress of the presidential election, the social changes had become the interesting issue. This fact is very interesting because the Head of State movie has the similar theme.